2005
DOI: 10.1177/1534734605280587
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Biomechanics of the Diabetic Foot

Abstract: In general, diabetic foot ulcers result from abnormal mechanical loading of the foot, such as repetitive moderate pressure applied to the plantar aspect of the foot while walking. Diabetic peripheral neuropathy causes changes in foot structure, affecting foot function and subsequently leading to increased plantar foot pressure, which is a predictive risk factor for the development of diabetic foot ulceration. Prevention of diabetic foot ulceration is possible by early identification of the insensitive foot, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
1
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 83 publications
(90 reference statements)
0
108
1
15
Order By: Relevance
“…A neuropatia diabética periférica (NDP), com uma incidência de 50 a 80%, dependendo do critério de avaliação utilizado (Bacarin, Sacco, & Hennig, 2009;Tapp et al, 2003;), parece surgir primariamente, como um distúrbio sensorial, causando perda gradual da sensibilidade à dor, da percepção da pressão plantar, temperatura e propriocepção e, posteriormente, como um distúrbio motor. Este último contribuindo para atrofia e fraqueza muscular, deformidades ósseas, desequilíbrio da mecânica do pé, déficit de equilíbrio, dificuldade para deambular e risco a quedas (Sacco, Noguera, Bacarin, Casarotto, & Tozzi, 2009;Van Schie, 2005).…”
Section: Equilíbrio Postural De Diabéticos | 31unclassified
“…A neuropatia diabética periférica (NDP), com uma incidência de 50 a 80%, dependendo do critério de avaliação utilizado (Bacarin, Sacco, & Hennig, 2009;Tapp et al, 2003;), parece surgir primariamente, como um distúrbio sensorial, causando perda gradual da sensibilidade à dor, da percepção da pressão plantar, temperatura e propriocepção e, posteriormente, como um distúrbio motor. Este último contribuindo para atrofia e fraqueza muscular, deformidades ósseas, desequilíbrio da mecânica do pé, déficit de equilíbrio, dificuldade para deambular e risco a quedas (Sacco, Noguera, Bacarin, Casarotto, & Tozzi, 2009;Van Schie, 2005).…”
Section: Equilíbrio Postural De Diabéticos | 31unclassified
“…These results suggested that diabetic neuropathic subjects with metatarsal head deformities adopt a strategy while walking to reduce plantar loads at the anterior parts of the foot that are structurally altered. These anterior areas of the plantar surface present more risk of ulcer formation than other areas 20,25,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Larger anterior contact area, higher posterior loads, and lesser loads at the metatarsal heads may be a result of an alteration of foot rollover mechanics from the heel rocker action at the initial contact to the propulsion by the forefoot rocker 27 . Neuropathic diabetic subjects may experience neuropathy pain during walking, and the metatarsal head prominences may worsen their symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pacientes diabéticos que apresentam insensibilidade, fraqueza muscular e diminuição da amplitude do movimento, têm maior risco para o desenvolvimento de ulcerações nos pés (SCHIE, 2005). O pé diabético representa uma das complicações mais mutilantes de grande impacto social e econômico (SBD, 2006;ADA, 2004a), sendo responsável por cerca de 50% das amputações dos membros inferiores nos EUA (HUMPHREY et al, 1994).…”
Section: Complicações Associadas Ao Diabetes Mellitus Tipounclassified